Early Onset Multiple Primary Tumors in Atypical Presentation of Cowden Syndrome Identified by Whole-Exome-Sequencing - Cavaillé, Mathias; Ponelle-Chachuat, Flora; Uhrhammer, Nancy; Viala, Sandrine; Gay-Bellile, Mathilde; Privat, Maud; Bidet, Yannick; Bignon, Yves-Jean (Frontiers in Genetics, 2018)
A family with an aggregation of rare early onset multiple primary tumors has been managed in our oncogenetics department: the proband developed four early onset carcinomas between ages 31 and 33 years, including acral melanoma, bilateral clear cell renal carcinoma (RC), and follicular variant of papillary thyroid carcinoma. The proband’s parent developed orbital lymphoma and small intestine mucosa-associated lymphoid tissue (MALT) lymphoma between 40 and 50 years old. Whole-exome-sequencing (WES) of the nuclear family (proband, parents, and sibling) identified in the proband a de novo deleterious heterozygous mutation c.1003C > T (p.Arg335∗) in the phosphatase and tensin homolog (PTEN) gene. Furthermore, WES allowed analysis of the nuclear family’s genetic background, and identified deleterious variants in two candidate modifier genes: CEACAM1 and MIB2. CEACAM1, a tumor suppressor gene, presents loss of expression in clear cell RC and is involved in proliferation of B cells. It could explain in part the phenotype of proband’s parent and the occurrence of clear cell RC in the proband. Deleterious mutations in the MIB2 gene are associated with melanoma invasion, and could explain the occurrence of melanoma in the proband. Cowden syndrome is a hereditary autosomal dominant disorder associated with increased risk of muco-cutaneous features, hamartomatous tumors, and cancer. This atypical presentation, including absence of muco-cutaneous lesions, four primary early onset tumors and bilateral clear cell RC, has not been described before. This encourages including the PTEN gene in panel testing in the context of early onset RC, whatever the histological subtype. Further studies are required to determine the implication of CEACAM1 and MIB2 in the severity of Cowden syndrome in our proband and occurrence of early onset MALT lymphoma in a parent.